Bi-Bi2S3 (at) C composite material and preparation method thereof

Through the preparation method of Bi-Bi2S3@C composite material, the problem of low photoelectric conversion efficiency of semiconductor Bi2S3 is solved, and the high light absorption and photoelectric conversion efficiency are improved, and the photoelectrochemical performance is good.

CN119400600APending Publication Date: 2025-02-07HUBEI UNIV OF EDUCATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411315250.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to improve the photoelectric conversion efficiency of semiconductor Bi2S3, and there are challenges in directly depositing metal Bi nanoparticles on the surface of Bi2S3.

Method used

Using a preparation method of Bi-Bi2S3@C composite material, by dissolving Bi(NO3)3·5H2O, Na2S·9H2O and urea in ethylene glycol solution, glucose is added after forming a black solution, and Bi- is generated through hydrothermal reaction. Bi2S3@C composite material. This method realizes the dual modification of Bi2S3 and improves the conductivity of the material through the formation of carbon element.

Benefits of technology

The high light absorption performance and photoelectric conversion efficiency of Bi-Bi2S3@C composite materials are realized, the photogenerated carrier density is enhanced, and the separation efficiency of electron-hole pairs is improved, with good application prospects in photoelectrochemical analysis and photoelectrocatalysis field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400600A_ABST
    Figure CN119400600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anode material preparation, and particularly relates to a Bi-Bi2S3 (at) C composite material and a preparation method thereof. The method comprises the following steps: dissolving Bi (NO3) 3.5 H2O in an ethylene glycol solution to obtain a solution A, dissolving Na2S. 9H2O in the ethylene glycol solution to obtain a solution B, and dissolving urea in the ethylene glycol solution to obtain a solution C; adding the solution B into the solution A to form a black solution, adding the solution C into the black solution, finally adding glucose, fully mixing to obtain a mixture, transferring the mixture into a reaction kettle, and fully reacting to obtain a reaction product, namely the Bi-Bi2S3-C composite material. The Bi-Bi2S3 (at) C composite material with anode photocurrent response is prepared through double modification of Bi2S3, the composite material has high light absorption performance and photoelectric conversion efficiency, and due to one-pot synthesis, additional modification after synthesis of Bi2S3 is not needed, and high efficiency and convenience are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anode material preparation, and specifically relates to a Bi-Bi2S3@C composite material and a preparation method thereof. Background Art

[0002] The narrow bandgap of semiconductor Bi2S3 makes the valence band and conduction band close to each other, resulting in the rapid recombination of photogenerated electron-hole pairs, which is not conducive to the separation and migration of photogenerated electrons and low photoelectric conversion efficiency. Bismuth (Bi) is considered to be an ideal substitute for precious metals, with obvious plasma resonance (SPR) effect and excellent light absorption performance in the visible and even near-infrared range. However, it is still a great challenge to directly deposit metallic Bi nanoparticles onto the surface of semiconductor Bi2S3. Summary of the invention

[0003] The purpose of the present invention is to provide a Bi-Bi2S3@C composite material with high light absorption performance and photoelectric conversion efficiency and a preparation method thereof in view of the above problems existing in the prior art.

[0004] To achieve the above objectives, the technical solution of the present invention is as follows:

[0005] In a first aspect, the present invention provides a method for preparing a Bi-Bi2S3@C composite material, the preparation method comprising:

[0006] S1. Dissolve Bi(NO3)3·5H2O in ethylene glycol solution to obtain solution A; dissolve Na2S·9H2O in ethylene glycol solution to obtain solution B; dissolve urea in ethylene glycol solution to obtain solution C;

[0007] S2. Add solution B to solution A to form a black solution, then add solution C to the black solution, and then add glucose, mix thoroughly to obtain a mixture, transfer the mixture to a reactor for thorough reaction, and after the reaction is completed, obtain a reaction product, which is the Bi-Bi2S3@C composite material.

[0008] In S2, the excess coefficient of Na2S·9H2O in the B solution is 1.2-1.8.

[0009] In S2, the molar ratio of urea in the C solution to Na2S·9H2O in the B solution is 2:1-2.5:1.

[0010] In S2, the reaction temperature of the reactor is 110-150°C and the reaction time is 10-15h.

[0011] In S2, the reaction product is washed, centrifuged, and dried at 60°C to obtain a Bi-Bi2S3@C composite material.

[0012] In a second aspect, the present invention provides a Bi-Bi2S3@C composite material, wherein the Bi-Bi2S3@C composite material is prepared by the aforementioned method.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The present invention uses bismuth nitrate pentahydrate as a bismuth source, sodium sulfide nonahydrate as a sulfur source, and glucose as a carbon source and reducing agent to synthesize a Bi-Bi2S3@C composite material with anode photocurrent response in one pot, thereby realizing the dual modification of Bi2S3. Glucose is used as a reducing agent to partially reduce Bi2S3 to monomer Bi, forming a Bi-Bi2S3 metal-semiconductor nanoheterojunction. Glucose is also used as a carbon source to form a carbon unit through thermal decomposition polymerization. The Bi-Bi2S3 nanoheterojunction is evenly dispersed on the surface of the carbon matrix, and finally forms a Bi-Bi2S3@C composite material containing metal bismuth with SPR effect, n-type semiconductor Bi2S3, and carbon unit with good conductivity. This method is efficient and convenient, and does not require additional modification after synthesizing Bi2S3. In addition, the coating property of glucose is good, and the structure of the obtained product is stable. Under illumination conditions, the SPR effect of Bi can enhance light absorption and increase the photogenerated carrier density of semiconductor Bi2S3. At the same time, the Bi-Bi2S3 nanoheterojunction is conducive to the separation of electron-hole pairs, and the carbon matrix can quickly conduct electrons to the anode, increasing the utilization rate of photoelectrons by the photoanode, so that the obtained Bi2S3@C composite material has good application prospects in the fields of photoelectrochemical analysis and photoelectrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 SEM images of pure Bi2S3 and Bi-Bi2S3@C composite materials.

[0016] Figure 2 This is the EDS spectrum of Bi-Bi2S3@C composite material.

[0017] Figure 3 This is the EDS spectrum of Bi-Bi2S3@C composite material.

[0018] Figure 4 XRD spectra of pure Bi2S3 and Bi-Bi2S3@C composite materials.

[0019] Figure 5 UV-Vis spectra of pure Bi2S3 and Bi-Bi2S3@C composite materials.

[0020] Figure 6 These are the typical EIS curves of bare ITO electrode, pure Bi2S3 modified electrode, and Bi-Bi2S3@C composite material modified electrode.

[0021] Figure 7 MS curves of pure Bi2S3 and Bi-Bi2S3@C composite materials.

[0022] Figure 8 These are the photocurrent-time curves of the pure Bi2S3 modified electrode and the Bi-Bi2S3@C composite material modified electrode with 0.1g, 0.2g, and 0.3g glucose doping amounts.

[0023] Fig. 9 is the target concentration curve corresponding to the photocurrent response.

[0024] Fig.10 This is a standard curve of target concentration-photocurrent response signal in the range of L-cysteine ​​concentration of 0.05 μM-10 μM.

[0025] Fig.11 The standard curve of target concentration-photocurrent response signal in the range of L-cysteine ​​concentration from 10 μM to 500 μM. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with specific implementations and drawings.

[0027] Embodiment 1:

[0028] A method for preparing a Bi-Bi2S3@C composite material is carried out in the following steps:

[0029] S1. Dissolve 1.23 g of Bi(NO3)3·5H2O in 5 mL of ethylene glycol solution to obtain solution A, dissolve 1.53 g of Na2S·9H2O in 10 mL of ethylene glycol solution to obtain solution B, and dissolve 0.91 g of urea in 20 mL of ethylene glycol solution to obtain solution C. Ultrasonicate the three solutions until they are completely dissolved using an ultrasonic cleaner; wherein the excess coefficient of Na2S·9H2O is 1.68, the excess coefficient of Na2S is the ratio of the amount of Na2S actually supplied by solution B to the amount of Na2S theoretically required by the reaction equation 2Bi(NO3)3+3Na2S→Bi2S3+6NaNO3, and the molar ratio of urea to Na2S·9H2O is 2.38:1;

[0030] S2. Transfer solution A to a 50 mL beaker, and slowly add solution B to solution A while stirring with a magnetic stirrer. After the reaction, a black solution is formed, indicating that Bi(NO3)3 reacts with Na2S to generate an amorphous precursor of Bi2S3. Then slowly add solution C to the above black solution. Urea acts as a mineralizer to regulate the morphology and size of the nanomaterial. After fully mixing, add 0.25 g of polyvinyl pyrrolidone (PVP) and 0.2 g of glucose respectively. After fully stirring and dissolving, stir continuously at room temperature for 1 h. Transfer the resulting mixture to the polytetrafluoroethylene lining of the hydrothermal reactor, then put the reactor lining into a stainless steel tank and tighten it, and put it in an oven and heat it to 120°C for 12 h.

[0031] S3. After the reaction is completed, the reactor is cooled naturally, the reactor lining is taken out from the stainless steel tank, the obtained reaction product is repeatedly washed with ethanol and water for several times, and centrifuged with a centrifuge, the centrifuged product is dried at 60°C, ground and collected, and a Bi-Bi2S3@C composite material is obtained.

[0032] To verify that the Bi-Bi2S3@C composite material of the present invention has good photoelectrochemical properties, pure Bi2S3 (without adding glucose and PVP, and the other preparation steps are the same as those in Example 1) and the composite material obtained in Example 1 were made into modified electrodes, and scanning electron microscopy and EDS analysis, XRD analysis, material light absorption analysis, AC impedance spectroscopy analysis, and Mott-Schottky curve analysis were performed.

[0033] 1. Preparation of modified electrodes

[0034] Indium tin oxide (ITO) conductive glass was used as the electrode substrate. The ITO conductive glass was first cut into small cubes. After ultrasonic cleaning, the electrode surface was blown dry, and then the electrode surface was sealed with 3M tape. A circular hole (aperture of 3.5 mm) for the modified material electrode was reserved with a puncher. A small piece of copper tape was also reserved to connect the circuit. 3 mg of the composite material obtained in Example 1 was weighed and ultrapure water was added to prepare a suspension by ultrasonic dispersion. Subsequently, 10 uL of the suspension was taken out and dripped on the surface of the ITO electrode and placed in an oven at 60°C for drying.

[0035] 2. Scanning electron microscopy and EDS analysis

[0036] In order to observe the surface morphology, the pure Bi2S3 and the composite material modified on the electrode substrate were analyzed by scanning electron microscope. The SEM images are as follows: Figure 1 shown. Figure 1 Figure A is the SEM image of pure Bi2S3. It can be seen from Figure A that the pure Bi2S3 modified on the electrode substrate is obviously accumulated. Figure B is the enlarged picture of Figure A. It can be seen from Figure B that the morphology of pure Bi2S3 is nanoparticles and the arrangement is relatively loose. Figure 1Figure C is the SEM image of the composite material. From Figure C, it can be seen that the composite material modified on the electrode substrate presents a smoother surface with some cracks, but there is no obvious agglomeration and accumulation of nanoparticles in pure Bi2S3. Figure D is an enlarged picture of Figure C. It can be seen that the nanoparticles of the composite material are more uniform and flat, and the nanoparticles are closely arranged and have a relatively uniform size.

[0037] To prove the successful preparation of Bi-Bi2S3@C photoelectrode, the elemental analysis of the composite material modified electrode surface was carried out using energy dispersive X-ray spectroscopy (EDS) testing technology. The obtained EDS spectrum is shown in Figure 2 As shown, Figure 2 It shows that the elements Bi, S, and C are evenly dispersed on the electrode surface; the EDS spectrum is as follows Figure 3 As shown, Figure 3 The presence of Bi, S, C and other elements in the Bi-Bi2S3@C composite material is also proved. In addition, due to the partial presence of zero-valent Bi, Figure 2 Element surface scan overlays and Figure 3 The content of Bi element in the medium energy spectrum is relatively better than that of S element.

[0038] 3. XRD analysis

[0039] XRD spectra can be used to determine the crystal properties, composition and purity of the corresponding substances. Figure 4 Curve a and curve b are the XRD spectra of pure Bi2S3 and Bi-Bi2S3@C composite materials, respectively. From curve a, it can be seen that all the diffraction peaks are consistent with the orthorhombic phase of Bi2S3 (JCPDS card number is No. 00-006-0333), and the main diffraction peaks at 24.98°, 25.21°, 28.64°, and 31.85° are attributed to the (111), (310), (230), and (221) crystal planes, respectively, and no other impurity peaks are observed. From curve b, we can see that the intensity of the diffraction peak corresponding to Bi2S3 is significantly reduced, and some new diffraction peaks appear; the diffraction peaks at 25.98°, 27.97°, 45.65°, and 45.83° correspond to the (012), (104), (006), and (113) crystal planes of the rhombohedral phase of metallic Bi (JCPDS card number is No. 00-044-1246), indicating that some Bi 3+The ions are reduced by glucose to generate elemental Bi; and the new diffraction peaks at angles of 26.08°, 41.72°, and 53.52° are attributed to the (002), (100), and (004) crystal planes of hexagonal carbon (JCPDS card number is No. 00-008-0415), which is related to the carbonization of glucose during the long-term solvent thermal reaction. In addition, by comparing curves a and b, it can be found that the diffraction peak of Bi2S3 in the composite material becomes broadened, which may be due to the increase in crystal stress caused by the reduction in grain size, thereby broadening the diffraction peak. The above XRD analysis further confirms the successful preparation of pure Bi2S3 and Bi-Bi2S3@C composite materials.

[0040] 4. Material light absorption analysis

[0041] The absorption of excitation light by photoactive materials is an important basis for measuring the photoelectrochemical performance of the material. Therefore, an ultraviolet-visible (UV-Vis) spectrophotometer is used to test the absorption intensity of visible light by the sample. Figure 5 Curve c and curve d show the UV-Vis spectra of pure Bi2S3 and Bi-Bi2S3@C composite material respectively. Compared with pure Bi2S3, Bi-Bi2S3@C composite material shows stronger visible light absorption ability, indicating that Bi-Bi2S3@C composite material can better utilize visible light to stimulate the generation of photogenerated carriers, thereby enhancing its potential as a photoactive material to construct high-performance photoelectrodes. This result may be related to the surface plasmon resonance effect of metallic Bi and the in-situ doping modification of dark carbon. By comparing the light absorption characteristics of the two materials, it is shown that Bi-Bi2S3@C composite material has good visible light absorption performance.

[0042] 5. AC impedance spectrum analysis

[0043] Electrochemical impedance spectroscopy (EIS) is used to study the electron transfer capacity during charge transfer on different electrode surfaces. 3- / 4- As a redox probe, Figure 6 EIS spectra of different modified electrodes are shown. Figure 6The middle curves j, k, and l show the typical EIS curves of bare ITO electrode, pure Bi2S3 modified electrode, and Bi-Bi2S3@C composite modified electrode, respectively. The electron transfer resistance of the electrode can be evaluated according to the arc radius fitted in the high-frequency region of the spectrum. Through data fitting, it is found that the Ret value of the bare ITO electrode is 104.5Ω, and its smaller Ret value indicates better electron transfer ability; the Ret value of the pure Bi2S3 modified electrode is 162.7Ω, and its Ret value is significantly larger than that of the bare ITO electrode, indicating that the Bi2S3 inorganic semiconductor material has been successfully fixed on the electrode substrate; compared with the pure Bi2S3 modified ITO electrode, the Ret value of the Bi-Bi2S3@C composite modified electrode is reduced to 131.4Ω, indicating that the use of Bi-Bi2S3@C composite material can reduce the electron transfer barrier and increase the charge transfer rate.

[0044] 6. Mott-Schottky curve analysis

[0045] The Mott-Schottky (MS) curve is used to determine the material properties such as the type of semiconductor material and the charge carrier concentration. Figure 7 The middle curve m and curve n represent the MS curves of pure Bi2S3 and Bi-Bi2S3@C composite material respectively. It can be seen that Figure 7 The slopes of the tangents of the two curves are both positive, indicating that Bi2S3 is an n-type semiconductor material, and the doping of metal Bi and C does not change the semiconductor type of Bi2S3. Since the charge carrier density is negatively correlated with the slope of the MS curve, the MS curve slope of the Bi-Bi2S3@C composite material is not as steep as that of the pure Bi2S3, and is significantly reduced, which means that the charge carrier density inside the composite material is improved, thereby improving the photoelectric conversion efficiency and photoelectric catalytic performance.

[0046] Embodiment 2:

[0047] The difference from Example 1 is that:

[0048] The added amount of glucose is 0.1 g, and the remaining preparation steps are the same as those in Example 1.

[0049] Embodiment 3:

[0050] The difference from Example 1 is that:

[0051] The added amount of glucose is 0.2 g, and the remaining preparation steps are the same as those in Example 1.

[0052] In order to find the composite material with the greatest improvement in photoelectric response, the amount of glucose added was optimized. The composite materials obtained in Examples 1-3 were made into different modified electrodes for photocurrent analysis; photoelectrochemical sensing applications were performed based on the optimized Bi-Bi2S3@C composite material.

[0053] 1. Photocurrent analysis

[0054] Under visible light irradiation, the photocurrent response of different modified electrodes was tested in 0.1M Na2SO4 electrolyte, and the following was plotted: Figure 6 The photocurrent-time (it) curve shown in Figure 8 In Figure E, curve e represents the pure Bi2S3 modified electrode, curves f, g, and h represent the composite material modified electrodes obtained in Examples 1-3, and Figure F is an enlarged view of curve h. Figure 8 It can be seen that when the bias voltage is set to 0V, all modified electrodes produce anodic photocurrent response to visible light. The anodic photocurrent value of the pure Bi2S3 modified electrode is 0.64μA. After being doped with different glucose contents, the Bi-Bi2S3@C modified electrode shows anodic photocurrents of different sizes. The photocurrent value of the composite material modified electrode with 0.1g glucose doping is 1.92μA, and the photocurrent value of the Bi-Bi2S3@C composite material modified electrode with 0.2g glucose doping is 2.84μA, which is significantly higher than the anodic photocurrent value of the pure Bi2S3 modified electrode. However, the photocurrent value of the composite material modified electrode with 0.3g glucose doping is 0.056μA, which is much smaller than the anodic photocurrent value of the pure Bi2S3 modified electrode, and there is no good photoelectrochemical response. Through the above photocurrent response comparison, the anodic photocurrent of the Bi-Bi2S3@C modified electrode with 0.2g glucose doping is the largest, showing the best photoelectrochemical response. It can be seen that the electron separation and transfer efficiency of this optimized Bi-Bi2S3@C composite material is improved, which improves the separation of photogenerated electron-hole pairs and prolongs the lifetime of photogenerated carriers, thereby enhancing the photoelectrochemical performance of the photoelectrode.

[0055] 2. Photoelectrochemical sensing applications

[0056] Due to the interaction between Bi-S bonds, thiol-containing L-cysteine ​​and Bi-based materials can be better bound to the photoelectrode and then oxidized by photogenerated holes, which further increases the anode photocurrent. Therefore, Bi-based materials can be used for L-cysteine ​​detection. Fig. 9 The target concentration corresponding to the photocurrent response is shown; Fig.10 The standard curve of target concentration-photocurrent response signal in the range of L-cysteine ​​concentration 0.05μM-10μM, ΔPI / μA=0.731lgC / μM+1.307, correlation coefficient R 2=0.999; Fig.11 The standard curve of target concentration-photocurrent response signal in the range of L-cysteine ​​concentration 10μM-500μM is ΔPI / μA=0.162lgC / μM+1.829. At a 3-fold signal-to-noise ratio, the detection limit of L-cysteine ​​is 0.013μM. The above results show that the Bi-Bi2S3@C composite modified electrode can be used for photoelectrochemical quantitative analysis of L-cysteine ​​with a low detection limit.

[0057] Embodiment 4:

[0058] The difference from Example 1 is that:

[0059] In S1, the excess coefficient of Na2S is 1.2; therefore, the added amount of Bi(NO3)3·5H2O is 1.23 g, the added amount of Na2S·9H2O is 1.09 g, and the added amount of urea is 0.65 g.

[0060] Embodiment 5:

[0061] The difference from Example 1 is that:

[0062] In S1, the excess coefficient of Na2S is 1.8; therefore, the added amount of Bi(NO3)3·5H2O is 1.23 g, the added amount of Na2S·9H2O is 1.64 g, and the added amount of urea is 0.98 g.

[0063] Embodiment 6:

[0064] The difference from Example 1 is that:

[0065] In S1, the molar ratio of urea to Na2S is 2:1; therefore, the added amount of Bi(NO3)3·5H2O is 1.23 g, the added amount of Na2S·9H2O is 1.53 g, and the added amount of urea is 0.77 g.

[0066] Embodiment 7:

[0067] The difference from Example 1 is that:

[0068] In S1, the molar ratio of urea to Na2S is 2.5:1; therefore, the added amount of Bi(NO3)3·5H2O is 1.23 g, the added amount of Na2S·9H2O is 1.53 g, and the added amount of urea is 0.96 g.

[0069] Embodiment 8:

[0070] The difference from Example 1 is that:

[0071] In S2, heat to 110°C in an oven and keep the temperature constant for 15 h.

[0072] Embodiment 9:

[0073] The difference from Example 1 is that:

[0074] In S2, the mixture was heated to 150°C in an oven and kept at a constant temperature for 10 h.

Claims

1. A method for preparing a Bi-Bi2S3@C composite material, characterized in that: The preparation method comprises: S1. Dissolve Bi(NO3)3·5H2O in ethylene glycol solution to obtain solution A; dissolve Na2S·9H2O in ethylene glycol solution to obtain solution B; dissolve urea in ethylene glycol solution to obtain solution C; S2. Add solution B to solution A to form a black solution, then add solution C to the black solution, and then add glucose, mix thoroughly to obtain a mixture, transfer the mixture to a reactor for thorough reaction, and after the reaction is completed, obtain a reaction product, which is the Bi-Bi2S3@C composite material.

2. The method for preparing the Bi-Bi2S3@C composite material according to claim 1, characterized in that: In S2, the excess coefficient of Na2S·9H2O in the B solution is 1.2-1.

8.

3. The method for preparing the Bi-Bi2S3@C composite material according to claim 1, characterized in that: In S2, the molar ratio of urea in the C solution to Na2S·9H2O in the B solution is 2:1-2.5:

1.

4. The method for preparing the Bi-Bi2S3@C composite material according to claim 1, characterized in that: In S2, the reaction temperature of the reactor is 110-150°C and the reaction time is 10-15h.

5. The method for preparing the Bi-Bi2S3@C composite material according to claim 1, characterized in that: In S2, the reaction product is washed, centrifuged, and dried to obtain a Bi-Bi2S3@C composite material.

6. A Bi-Bi2S3@C composite material, characterized in that: The Bi-Bi2S3@C composite material is prepared by the method described in any one of claims 1-5.